A bovine teat papilloma specimen harboring Deltapapillomavirus (BPV-1) and Xipapillomavirus (BPV-6) representatives - Marlise Pompeo Claus; Michele Lunardi; Amauri Alcindo Alfieri; Rodrigo Alejandro Arellano Otonel; Lara Munique Ferracin; Maria Helena Pelegrinelli Fungaro; Alice Fernandes Alfieri (Brazilian Archives of Biology and Technology, 2009)
The common occurrence of multiple papillomavirus infections has been shown in several studies involving the human host. However, investigations with the aim of identifying mixed papillomavirus infections in cattle have been conducted only recently. In the current work we describe a co-infection with two different bovine papillomavirus (BPV) types that was identified in a bovine teat papilloma. The skin wart was obtained from a cow belonging to a Brazilian beef herd. A PCR assay was carried out with the FAP primer pair, which amplifies a partial segment of the L1 gene (approximately 478 bp), and the amplicon was submitted to direct sequencing. Because nucleotide sequences with satisfactory quality scores were not obtained, the amplicon was cloned and further sequencing, involving ten selected clones, was performed. The sequence analysis of the cloned inserts revealed the presence of two different BPV types. BPV-1 (Deltapapillomavirus genus) was detected in six clones, while BPV-6 (Xipapillomavirus genus) was detected in four clones. This finding confirms the presence of BPV co-infection associated with cutaneous papillomatosis in cattle. Em seres humanos, as infecções múltiplas pelo papilomavírus têm sido demonstradas em vários estudos. Em bovinos, somente recentemente foram conduzidas investigações com o objetivo de avaliar infecções mistas pelo papilomavírus. O presente trabalho teve como objetivo descrever a co-infecção por dois tipos de papilomavírus bovino (BPV) em um papiloma de teto. A amostra clínica foi obtida de uma vaca pertencente a um rebanho de corte localizado na região norte do estado do Paraná, Brasil. Inicialmente, a técnica de PCR foi realizada com o par de oligonucleotídeos iniciadores FAP, que amplificam um segmento do gene L1, sendo que o amplicon gerado foi submetido ao sequenciamento direto. Entretanto, como as sequências obtidas não apresentaram qualidade aceitável, o amplicon foi clonado e dez clones foram selecionados para um novo sequenciamento. A análise das sequências dos insertos revelou a presença de dois diferentes tipos de BPV. O BPV-1 (gênero Deltapapillomavirus) foi detectado em seis clones, enquanto o BPV-6 (gênero Xipapillomavirus) foi detectado em quatro clones. Esse resultado confirma a ocorrência da co-infecção pelo BPV associada a papilomas cutâneos em bovinos.